2019
DOI: 10.1016/j.heliyon.2019.e02329
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration potential of natural vegetation under grazing influence in Southern Tigray, Ethiopia: implication for climate change mitigation

Abstract: The management influence on carbon sequestration potential of different land use types are least known at the national level. This research was conducted to assess the impact of area exclusion on carbon sequestration potential in the two land use systems: protected natural vegetation (PNV) and communal grazing land (CGL). Data of vegetation, litter, and soils were collected using systematic sampling methods, laying 19 transects and 62 quadrats each with 20 m × 20 m for trees, 5 m × 5 m sub-quadrats for shrubs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
4
19
1
Order By: Relevance
“…The high contribution of living biomass over soil to overall carbon were in agreement with Meena et al (2019) who reported that living plant biomass contribute about 40% to 49% and Simegn et al, 2014 who reported about 57% of the total carbon from living biomass. Abere et al (2017) and Atsbha et al (2019) also reported findings that were within the range found in the study. This was, however contrary to the findings by other studies undertaken in nearly similar dry ecosystems (Dabasso et al, 2014;Solomon et al, 2018;Gebeyehu et al, 2019) who found soil to contribute the greatest carbon storage potential than the other carbon pools.…”
Section: Biomass Carbon Stock and Carbon Financingsupporting
confidence: 88%
See 1 more Smart Citation
“…The high contribution of living biomass over soil to overall carbon were in agreement with Meena et al (2019) who reported that living plant biomass contribute about 40% to 49% and Simegn et al, 2014 who reported about 57% of the total carbon from living biomass. Abere et al (2017) and Atsbha et al (2019) also reported findings that were within the range found in the study. This was, however contrary to the findings by other studies undertaken in nearly similar dry ecosystems (Dabasso et al, 2014;Solomon et al, 2018;Gebeyehu et al, 2019) who found soil to contribute the greatest carbon storage potential than the other carbon pools.…”
Section: Biomass Carbon Stock and Carbon Financingsupporting
confidence: 88%
“…Further, Zhao et al (2019) indicated that the variation in data sources, estimation methods, scope of study area and environmental variables with different biotic and abiotic conditions and response to climate change may lead to significant variation in carbon storage estimates. Moreover, Keiluweit et al (2015) The mean carbon stock from this study was slightly lower compared to those reported for nearly similar landscape in northern Kenya and Ethiopia (Dabasso et al, 2014;Gebeyehu et al, 2019), but was within the reported range in other dry forest-landscapes (Tiessen et al, 1998;Glenday, 2008;Simegn et al, 2014;Abere et al, 2017;Atsbha et al, 2019;Srinivas and Sundarapandian, 2019). The effects of vegetation and landscape type were significant on carbon stocks.…”
Section: Biomass Carbon Stock and Carbon Financingsupporting
confidence: 67%
“…In practice, the underground C stocks of plants are typically included in soil C stocks due to methodological difficulties in separating living roots from various soil organic matter components. For woody species, root biomass is commonly estimated to be 27% of aboveground biomass (Atsbha 2019). For agricultural crops, an agroecosystem model (Crop-DNDC) integrates detailed crop growth algorithms with an existing soil biogeochemical model and simulates C, nitrogen, and water cycles in agroecosystems with a relatively complete scope (Zhang et al 2002;Li et al 1992).…”
Section: Existing Assessment Methods For the Carbon Storage And Uptake Of Shrubs And Herbaceous Plantsmentioning
confidence: 99%
“…The global demand for beef, mutton, and dairy was estimated to increase by 13.9%, 22.0%, and 22.2%, respectively, between 2011 and 2020 (OECD-FAO, 2011). The grazing management mode could strongly impact the regional richness, biomass, carbon sequestration capacity, and ecological health of grasslands (Atsbha et al, 2019). Therefore, animal husbandry and grassland ecosystem services are complementary and mutually restricted.…”
Section: Introductionmentioning
confidence: 99%